A novel transcutaneous, non‐focused ultrasound energy delivering device is able to induce subcutaneous adipose tissue destruction in an animal model. Issue 1 (29th October 2016) - Levi, Assi; Amitai, Dan Ben; Lapidoth, Moshe
Abstract : Background and Objectives: The understanding that adipocytes are greatly influenced by thermal changes combined with the advancement of non‐invasive ultrasound technologies have led to the application of ultrasound as an energy source to induce thermal fat destruction. While application of high intensity focused, ultrasound energy have been widely explored, there is far less information regarding the effects of non‐focused ultrasound on adipose tissue. The purpose of this study was to characterize the effects of a novel transcutaneous, multi‐elements, non‐focused ultrasound energy regimen in an animal model, as a proof‐of‐concept of its potential to treat non‐invasive subcutaneous benign tumors. Materials and Methods: The non‐invasive transcutaneous ultrasound system prototype (LUMENIS, Ltd., Yoqneam, Israel) was applied to thermally induce adipocytes' death. During treatment, the ultrasound energy was transmitted into the subcutaneous adipose tissue (SAT) of 12 domestic adult female pigs. Two modes of operation (long and short), which differ in both the acoustic energy applied to the tissue and in their time durations (i.e., differ in their power settings), were used in this study. Efficacy and safety assessments included: Temperature measurement of skin and subcutaneous adipose tissue (SAT) visual inspection and ultrasound imaging of the thermally affected areas, histopathological assessment of tissue samples using hematoxylin & eosin, and Masson's trichrome stains and in situ cell death detection kit for apoptosis assessment. Results: The long and short treatment modes led to a 13.2°C and 17.8°C rise from baseline, respectively, in the SAT, whereas skin surface temperature was practically unaffected. Visual, ultrasonographic, and histopathological evaluation of the treated area showed SAT ablation. No treatment‐related changes were observed in the epidermis, dermis subcutaneous muscle and nerves, or in livers and kidneys of treated animals. Additionally, no significant changes from baseline in blood‐ and urine‐borne analytes were detected post‐treatment. Conclusions: The novel transcutaneous, multi‐elements, non‐focused ultrasound energy regimen used in this study, proved effective in non‐invasively ablating SAT in an animal model. The usage of low energy settings such as in the current study might reduce unwanted side effects related to high energy application. Lasers Surg. Med. 49:110–121, 2017. © 2016 Wiley Periodicals, Inc.